Total fitness : an advanced training guide for the sportsperson - Martin, Nita A. (The Crowood Press, 2010)
Introduces the various components of fitness, and examines the benefits of training. This book describes and illustrates exercises for developing the following: strength, strength endurance, power, plyometrics, stamina, speed, agility, coordination, posture, flexibility and balance